Current Advancements and Limitations of Gene Editing in Orphan Crops - Venezia, Matthew; Creasey Krainer, Kate M. (Frontiers in Plant Science, 2021)
Gene editing provides precise, heritable genome mutagenesis without permanent transgenesis, and has been widely demonstrated and applied in planta. In the past decade, CRISPR/Cas has revolutionized the application of gene editing in crops, with mechanistic advances expanding its potential, including prime editing and base editing. To date, CRISPR/Cas has been utilized in over a dozen orphan crops with diverse genetic backgrounds, leading to novel alleles and beneficial phenotypes for breeders, growers, and consumers. In conjunction with the adoption of science-based regulatory practices, there is potential for CRISPR/Cas-mediated gene editing in orphan crop improvement programs to solve a plethora of agricultural problems, especially impacting developing countries. Genome sequencing has progressed, becoming more affordable and applicable to orphan crops. Open-access resources allow for target gene identification and guide RNA design and evaluation, with modular cloning systems and enzyme screening methods provide experimental feasibility. While the genomic and mechanistic limitations are being overcome, crop transformation and regeneration continue to be the bottleneck for gene editing applications. International collaboration between all stakeholders involved in crop improvement is vital to provide equitable access and bridge the scientific gap between the world’s most economically important crops and the most under-researched crops. This review describes the mechanisms and workflow of CRISPR/Cas in planta and addresses the challenges, current applications, and future prospects in orphan crops.